Lutter Contre Les Inégalités Sociales De Santé 2008
DOI: 10.3917/ehesp.niewe.2008.01.0057
|View full text |Cite
|
Sign up to set email alerts
|

Lutter contre les inégalités sociales de santé

Abstract: Réduire les inégalités sociales de santé : aporie, épistémologie et défis 1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…Our first theme demonstrated that there lacked a unified vision of SIH for all sectors involved in large-scale testing in Montréal. It has been argued elsewhere that the ways in which different actors understand and represent SIH (perception of SIH), their causes and their consequences influence how health interventions are designed (strategy to tackle SIH) [32]. In our study, it seems contradictory that many participants recognised the need to reach vulnerable groups not to exacerbate inequities, but that the overarching strategy to large-scale testing was population-wide (as demonstrated by our second theme).…”
Section: Discussionmentioning
confidence: 68%
“…Our first theme demonstrated that there lacked a unified vision of SIH for all sectors involved in large-scale testing in Montréal. It has been argued elsewhere that the ways in which different actors understand and represent SIH (perception of SIH), their causes and their consequences influence how health interventions are designed (strategy to tackle SIH) [32]. In our study, it seems contradictory that many participants recognised the need to reach vulnerable groups not to exacerbate inequities, but that the overarching strategy to large-scale testing was population-wide (as demonstrated by our second theme).…”
Section: Discussionmentioning
confidence: 68%
“…However, in its desire to be accredited by the Council on Education for Public Health (CEPH ), the UdeM has, over time, lost its diversity by refocusing on traditional public health, leaving little room for participatory approaches and community health. 12 On the other hand, in Quebec City, teaching focused on community health has always prevailed, with a multifaculty doctorate that is not without enormous challenges of disciplinary power struggles 13 and struggles to recruit students. Moreover, although the UdeM School of Public Health has just appointed a Black dean of Haitian origin for the first time in its history, teachers representing this cultural diversity are very rare.…”
Section: Alarming Findings On the Lack Of Diversitymentioning
confidence: 99%
“…Cette recherche exploratoire montre que la démarche de l'évaluation réaliste est faisable, mais il conviendrait de la reproduire à une plus grande échelle pour accéder à l'ensemble des connaissances nécessaires à une compréhension plus exhaustive des mécanismes favorables à la réduction des inégalités sociales de santé en France. épistémologique (5,6). Comment, en effet, faire la démonstration de l'efficacité d'interventions aussi complexes et multisectorielles sans avoir recours aux devis expérimentaux peu appropriés dans de tels contextes ?…”
Section: Perception De Quelques Mécanismes Favorables à La Réduction Des Inégalités Sociales De Santé En Franceunclassified
“…épistémologique (5,6). Comment, en effet, faire la démonstration de l'efficacité d'interventions aussi complexes et multisectorielles sans avoir recours aux devis expérimentaux peu appropriés dans de tels contextes ?…”
unclassified